2018
DOI: 10.1075/jaic.16019.han
|View full text |Cite
|
Sign up to set email alerts
|

Establishing validity among pre-school children

Abstract: This paper lays out theoretical considerations and first analyses on the giving of and asking for reasons among preschool children age 3–7 in natural child-child play interaction. We attempt to give an integrated, multimodal analysis of the verbal, paraverbal and extraverbal means of these reasoning activities. In our data we find many instances of younger children who are giving reasons during play interaction. Often these reasoning activities do not occur in an open conflict and are not primarily directed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In this case they also exhibit them to Juno, a girl who for some time plays along with the two boys (line 251) but never engages in a conversation with them. Interestingly, we find similar sequences in play situations and situations that involve reasoning by other children (Hannken-Illjes and Bose, 2018). Here the children will point out to each other that they are very competent together in what they are doing.…”
Section: Yessupporting
confidence: 66%
See 3 more Smart Citations
“…In this case they also exhibit them to Juno, a girl who for some time plays along with the two boys (line 251) but never engages in a conversation with them. Interestingly, we find similar sequences in play situations and situations that involve reasoning by other children (Hannken-Illjes and Bose, 2018). Here the children will point out to each other that they are very competent together in what they are doing.…”
Section: Yessupporting
confidence: 66%
“…However, the fact that children do not exhibit elaborate argumentative abilities in disputes should not lead to the conclusion that they do not have them at their command. Our own studies have shown that preschool children are able to engage in argumentation in either fictional disputes in role play (Bose 2003;Bose and Hannken-Illjes 2016), or in cooperative interaction in play settings (Hannken-Illjes and Bose 2018). There are further studies that support these findings and that shall be referred to in the following section.…”
Section: Entry Points Into Studying Argumentation Among Childrenmentioning
confidence: 72%
See 2 more Smart Citations
“…We note further that the common denominator of the sample as a whole is a view of opposition, disagreement, or a difference of opinion as a defining minimal feature of children's argumentation. We will argue that this is the case even in studies that propose to see cooperativity as representing a possible initial argumentative framing (e.g., Hannken-Illjes & Bose, 2018, since opposition is, on our reading, not denied but rather presupposed here as well. Hence, given that the structural aspect, subsuming the oppositional antecedent, is inherent in all argumentation, one can argue that, within the field of argumentation in the early years, the structural-discursive dimension of Schwarz and Baker's (2017) model represents a continuum, stretching from more to less structural specificity along, primarily, the dialogic dimension.…”
Section: Summarizing Discussionmentioning
confidence: 79%